Quantification of UV protecting additives in ethylene-vinyl acetate copolymer encapsulants for photovoltaic modules with pyrolysis-gas chromatography-mass spectrometry. (15th January 2023) - Heidrich, Robert; Mordvinkin, Anton; Gottschalg, Ralph
Abstract: Reliability of polymeric encapsulants is being assured using suitable additives. Especially UV absorbers and UV stabilizers are important to protect the encapsulants from solar radiation. Identifying the additives and their quantities is essential for quality control and lifetime predictions. In this work a new method for quantitative additive characterization by pyrolysis-gas chromatography-mass spectrometry (PY-GCMS) is presented. A general workflow for qualitative analysis and additive quantification is proposed which is based on solvent-free sample preparation. A series of polymer film samples has been prepared with different additive concentrations for method development and validation. Using the two-step thermo desorption extraction all admixed additives can be detected. Furthermore, it was shown that the desorption behavior of the UV protecting additives dissolved in n-hexane strongly differs from the desorption of additives bound inside the polymer matrix. Thus, the use of reference samples is required for calibration. Finally, using verification samples as well as one commercial polymer film, the determination of the mass fractions of the studied UV absorber and UV stabilizer was shown to be possible with high accuracy. While this work is focused on ethylene-vinyl acetate copolymer (EVA) as encapsulant for photovoltaic modules, the derived methodology is very likely directly transferable to other encapsulant and additive compositions. Highlights: Determination of the absolute UV absorber and UV stabilizer content in EVA films with PY-GCMS. Qualitative and quantitative analysis of EVA additives. Transferable additive quantification procedure for polymeric encapsulants.